2021
DOI: 10.1080/15563650.2021.1916519
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neuromuscular function by conjoint actions of organophosphorus insecticide metabolites omethoate and cyclohexanol with implications for treatment of respiratory failure

Abstract: Impaired neuromuscular function by conjoint actions of organophosphorus insecticide metabolites omethoate and cyclohexanol with implications for treatment of respiratory failure, Clinical Toxicology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(41 citation statements)
references
References 88 publications
5
36
0
Order By: Relevance
“…We showed previously that 20 mM cyclohexanol has only a weak effect on AChE activity (Dissanayake et al . 2021) but 5 μM neostigmine was sufficient to completely inhibit AChE activity in FDB muscle homogenates (R. Chou and R. R. Ribchester, unpublished data). Figure 2 and shows EPP responses in a continuous recording from an FDB muscle fibre incubated in 5 μM neostigmine, before and after adding 20 mM cyclohexanol.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…We showed previously that 20 mM cyclohexanol has only a weak effect on AChE activity (Dissanayake et al . 2021) but 5 μM neostigmine was sufficient to completely inhibit AChE activity in FDB muscle homogenates (R. Chou and R. R. Ribchester, unpublished data). Figure 2 and shows EPP responses in a continuous recording from an FDB muscle fibre incubated in 5 μM neostigmine, before and after adding 20 mM cyclohexanol.…”
Section: Resultsmentioning
confidence: 93%
“…Subsequently, we showed that cyclohexanol administered either intravenously in vivo or added to medium bathing isolated murine nerve–muscle preparations mimicked the impairment of neuromuscular function associated with insecticide gavage, in a temperature‐sensitive fashion (Dissanayake et al . 2021). Our aim in the present study was to establish the synaptic mechanisms underlying these myasthenic effects of cyclohexanol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations